Interseismic uplift and strain accumulation in Nepal Himalaya - Kapur, Nipun; Agrawal, R. C. (Journal of Nepal Geological Society, 1998)
Savage (1983, 1995) and Thatcher and Rundle (1984) have postulated elastic half space and viscoelastic coupling models of strain accumulation and earthquake occurrences at the upper surface of the subducting lithospheric plate called detachment. These models infer the presence of a locked zone on the detachment during interseismic periods. The analysis based on interseismic uplift data of about two decades in Nepal Himalaya indicates absence of the postulated locked zone and instead suggests occurrence of thrust fault type (up dip) slip on the entire detachment (Jackson and Bilham, 1994). A question then arises as to whether the strains are accumulating at all in this region. Further, if strains are accumulating we may like to investigate the process responsible. The answer is provided by a plausible model visualising strain accumulation due to differential motion of the medium particles on the detachment and those above it. This relative down dip motion of the medium particles on the detachment may be occurring even if the subducting and the overriding plates are not fully coupled or locked. Sections with high coupling on the detachment would have accumulated larger strains compared to those with low coupling. A temporal decrease in up dip slip rate on the detachment, by virtue of increase in coupling or strain hardening, further represents interseismic accumulation of shear strains. On the other hand, a temporal increase in up dip slip rate, when activates unstable motion, may culminate into occurrence of a large earthquake. This model explains the observed elevation changes in the Himalaya and corresponding inference of up dip slip on the detachment. It also provides plausible justification to the occurrence of moderate and great earthquakes on a part of the detachment lying primarily below the Lesser-Higher Himalaya.